Who Chooses Whom? Syndication, Skills and Reputation - Tereza Tykvová (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
Syndication, which is a joint realization of one project/one investment by several capital providers, is a long existing phenomenon that plays a central role in many financial market segments. Within this paper we develop a theoretical model focusing on the dynamic aspect of syndication, namely the know-how transfer between syndication partners and their ability to learn. The core of the analysis checks whether repeated relationships and, thus, reputational concerns outweigh the temptation to renege on a given contract. Throughout the paper, we investigate two key topics. The first consists of the conditions under which investors syndicate their deals. The second focuses on who chooses whom. We show that experienced financiers may partner with either other experienced investors (in order to raise the success probability of a project) or with unskilled investors (who can gain knowledge). We further demonstrate that sometimes the syndication is impeded because the financier believes that his partner has strong incentives to either renege on a contract (hold-up problem) or to shirk (moral hazard problem).
Keywords: D83; L14; G32; 330; Syndication; Hold-up; Reputation; Learning; Projektfinanzierung; Investition; Finanzierung; Unternehmenskooperation; Wissenstransfer; Lernprozess; Prestige; Sunk Costs; Theorie